Aristofane, poeta comico per antonomasia nei testi di Luciano? - Martina Tosello (Annali Online dell'Università di Ferrara. Sezione Lettere, 2016)
As a satirist, Lucian looks up to Aristophanes as one of his main literary models and mentions him thrice across his corpus in programmatic passages. Moreover, he quotes a few whole verses (seven, overall) to be attributed to a κωμικός. Such an ambiguous indication may refer to virtually any satirist belonging to archaia or nea. Hence, attributing most of those verses to a specific author is quite difficult: Kassel-Austin place three of those fragments in Adespota and one in Aristophane's dubia. Through an analysis of contexts and quotation modes, my aim is to find out whether ὁ κωμικός refers to par excellence comic poet Aristophanes, thereby confirming his importance within Lucian’s work.